2006
DOI: 10.3892/ijo.29.2.365
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic interaction of 5-aminolevulinic acid-based photodynamic therapy with simultaneous hyperthermia in an osteosarcoma tumor model

Abstract: Abstract. In this study, the effectiveness and mechanism of combination therapy of 5-aminolevulinic acid-based photodynamic therapy (ALA-PDT) with simultaneous hyperthermia (HT) on human-derived osteosarcoma in vivo were examined. A tumor model was prepared by subcutaneously implanting human osteosarcoma into nude mice and local injection of ALA was selected as the administration route. This study demonstrated that both ALA-PDT and the combination of ALA-PDT with HT exhibited significant inhibitory effects on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…30 CAIX is a downstream biomarker of hypoxia inducible factor (HIF-1α), upregulated under hypoxic conditions, making CAIX closely associated with hypoxia. [31][32][33] Our observation of high CAIX expression in PDT-treated tumors is consistent with the expectation that photodynamic action would create a hypoxic environment.…”
Section: Resultssupporting
confidence: 75%
“…30 CAIX is a downstream biomarker of hypoxia inducible factor (HIF-1α), upregulated under hypoxic conditions, making CAIX closely associated with hypoxia. [31][32][33] Our observation of high CAIX expression in PDT-treated tumors is consistent with the expectation that photodynamic action would create a hypoxic environment.…”
Section: Resultssupporting
confidence: 75%
“…Furthermore, it has been shown that wIRA reduces pain in chronic wounds, warts, herpes, scleroderma, gonarthrosis and spondylitis (Fuchs et al, 2004; Hartel et al, 2006). Applying wIRA would enhance the effects of PDT since heating has some synergistic effect when applied together with PDT (Waldow et al, 1985;Kelleher et al, 2003;Yanase et al, 2006). The use of antimicrobial PDT (APDT) could therefore potentially improve the tissue healing process in a number of dental procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we provide additional knowledge concerning its molecular action in cancer cells. Understanding the precise pathways involving the induction of apoptosis may help in the development of treatment modalities of PDT in malignant diseases, either alone or in combination with other therapeutic arms (13,41).…”
Section: Discussionmentioning
confidence: 99%